2006
DOI: 10.1139/f05-271
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends of bloater (Coregonus hoyi) recruitment in Lake Michigan: evidence for the effect of sex ratio

Abstract: Long-term population trends are generally explained by factors extrinsic (e.g., climate, predation) rather than intrinsic (e.g., genetics, maternal effects) to the population. We sought to understand the long-term population dynamics of an important native Lake Michigan prey fish, the bloater Coregonus hoyi. Over a 38-year time series, three 10-to 15-year phases occurred (poor, excellent, and then poor recruitment) without high interannual variability within a particular phase. We used dynamic linear models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 49 publications
3
70
0
Order By: Relevance
“…In a relative sense, however, the CPUE of recruits was reXective of relative year-class strength. In Lake Michigan, for example, bloaters fully recruit to the bottom trawl at age 3 (Bunnell et al 2006), but there is a strong positive correlation (r = 0.68; P < 0.0001) between age-0 CPUE and age-3 CPUE for the year-classes from 1962 up to and including 2000 (D .B. Bunnell, unpublished data).…”
Section: Data Processing and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a relative sense, however, the CPUE of recruits was reXective of relative year-class strength. In Lake Michigan, for example, bloaters fully recruit to the bottom trawl at age 3 (Bunnell et al 2006), but there is a strong positive correlation (r = 0.68; P < 0.0001) between age-0 CPUE and age-3 CPUE for the year-classes from 1962 up to and including 2000 (D .B. Bunnell, unpublished data).…”
Section: Data Processing and Analysesmentioning
confidence: 99%
“…php (accessed 24 November 2008). We chose winter because winter has been hypothesized as a critical period for survival of bloater eggs and embryos (e.g., Rice et al 1987;Bunnell et al 2006). We chose summer because bloater larvae occupy the epilimnion during these months (Rice et al 1987), and thus may be inXuenced by air temperature to a greater extent than the adult life stage that occupies the hypolimnion.…”
Section: Data Processing and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent stock-recruit modeling for bloater in Lakes Michigan and Huron indicated that sex ratio had an important impact on recruitment (Collingsworth et al 2014). Based on ages of bloater captured in the bottom trawl survey, relatively high levels of age-0 bloater in 2007-2009 acoustic surveys ( Figure 5) are reflected in age composition of YAO bloaters in recent years, as most of the larger bloater aged in 2009-2011 were hatched in 2007-2009, adding support to the belief that bloater become fully recruited to the bottom trawl by age-3 (Bunnell et al 2006). Data from both acoustic and bottom trawl surveys suggest that recruitment has not been sufficient to offset mortality.…”
Section: Discussionmentioning
confidence: 84%
“…River Darters also generally appear to have a skewed sex ratio, with a predominance of females in most of the assessed populations. This phenomenon is found in many fishes, and there are a number of explanations for differential survival of the sexes including increased mortality due to predation, differences in growth rate and an associated survival trade-off, or differences in reproductive activity or maturation schedule [20]. The high female dominance may indicate poor recent recruitment events for these River Darter populations if males have lower survival and females become dominant at older ages.…”
Section: Discussionmentioning
confidence: 99%